Manganese transport in mammals by zinc transporter family proteins, ZNT and ZIP - Hitomi Fujishiro; Taiho Kambe (Elsevier, 2022)
Manganese (Mn) is an essential trace element required for various biological processes. However, excess Mn causes serious side effects in humans, including parkinsonism. Thus, elucidation of Mn homeostasis at the systemic, cellular, and molecular levels is important. Many metal transporters and channels can be involved in the transport and homeostasis of Mn, and an increasing body of evidence shows that several zinc (Zn) transporters belonging to the ZIP and ZNT families, specifically, ZNT10, ZIP8, and ZIP14, play pivotal roles in Mn metabolism. Mutations in the genes encoding these transporter proteins are associated with congenital disorders related to dysregulated Mn homeostasis in humans. Moreover, single nucleotide polymorphisms of ZIP8 are associated with multiple clinical phenotypes. In this review, we discuss the recent literature on the structural and biochemical features of ZNT10, ZIP8, and ZIP14, including transport mechanisms, regulation of expression, and pathophysiological functions. Because a disturbance in Mn homeostasis is closely associated with a variety of phenotypes and risk of human diseases, these transporters constitute a significant target for drug development. An understanding of the roles of these key transporters in Mn metabolism should provide new insights into pharmacological applications of their inhibitors and enhancers in human diseases.